Effect of Kelussia odoratissima Mozaff essential oil on promastigot form of Leishmania major (in vitro) - Pirali Kheirabadi Khodadad; Saei Dehkordi Siavash; Kheibari Parviz (Shahrekord University of Medical Sciences, 2015)
Introduction: Leishmaniasis is a zoonotic disease caused by a protozoan of the genus Leishmania. In this study, the effects of Kelussia odoratissima Mozaff essential oil on the promastigot form of Leishmania major were studied. Methods: In this study, the effects of Kelussia odoratissima Mozaff essential oil on the promastigot form of Leishmania major were assessed by calculating the average number of surviving promastigots after exposure to different concentrations of essential oil, relative to the control Glucantime, at different time intervals. To achieve this, various essential oil concentrations (7.5 μl, 15 μl, 25 μl, 35.25 μl, 50 μl) were added to parasites. Different groups in this study were kept in a 26°C incubator under identical conditions. 24, 48 and 72 hours after incubation, living promastigots were counted. Results: The effect of the essential oil of Kelussia odoratissima Mozaff differed from the negative and positive controls and depended on the concentration: higher concentrations (35.25 μl, 50 μl) had a stronger effect on promastigots, causing total mortality. Conclusion: This study showed that Kelussia odoratissima Mozaff essential oil had effects on promastigot form of Leishmania major. So it might be possible to use the essential oil of Kelussia odoratissima instead of chemical drugs.